Factores que desalientan la formalización de los comerciantes de jugos de la 1era cuadra de la calle 9 de diciembre, mercado de Belén, Iquitos, periodo 2019 - Lopez Laulate, Rosa Amelia (2021)
The general objective of the execution of this investigation was to determine what are the factors that discourage the formalization of Juice merchants on the 1st block of December 9th Street, Mercado Belén, Iquitos, period 2019. According to the data obtained, it was determined that the factors that discourage formalization are the average level of tax culture they have, the difficulty they find to meet some requirements for their formalization as stated by fifty-six percent. (56%) of the merchants, ignorance of the facilities that the state provides to microentrepreneurs, sixty-nine percent (69%) manifest it in their responses to the questionnaire, how complex the tax regulations are for formalization , as stated by sixty-nine percent (69%) of merchants and the poor perception they have of the state's use of the taxes collected, as expressed by eighty-seven percent (87%) of merchants. This research work will serve as a contribution to the municipalities and other authorities to gain insight into the factors that discourage the formalization of juice merchants on the 1st block of street 9 de December, Mercado de Belén, Iquitos.